The Path Analysis of Body Mass Index, Physical Exercise, Sleep Quality, and Parental Education on Physical Fitness among Male Adolescences - Hayu Andita Satriani; Dono Indarto; Yulia Lanti Retno Dewi (Journal of Health Promotion and Behavior, 2018)
Background: Rapid physical growth occurs during adolescence period. Physical fitness is a key indicator for general health, which shows individual ability of cardiorespirationand skeletal muscles to adapt to physical activity load. Many factors can influence physical fitness such as Body Mass Index for age (BMI/age), physical exercise, sleep quality and parental education. The purpose of this study was to analyze the relationship of BMI/age, physical exercise, sleep quality and parental education with physical fitness levels among male adolescences.Subjects and Methods:  This cross-sectional study was conducted in three private senior high schools at the Gondokusuman district, Yogyakarta. Study subjects were selected using the fixed exposure sampling technique with inclusion criteria: male adolescence who aged 15-18 years old and had normal or more BMI/age. The dependent variable was physical fitness. The independent variables were BMI/age, physical exercise, sleep quality, and parental education.  The data were collected by questionnaire and analyzed by path analysis.Results: Physical exercise (b= 0.32; SE= 0.46; p<0.001) and BMI/age (b= -2.87; SE= 0.27; p= <0.001) were directly related to physical fitness. Indirect relationship was found inparent education and sleep index score with physical fitness through physical exercise. Interestingly, BMI/age had direct and indirect relationship to physical fitness.Conclusion: BMI/age is a predominant factor that influences physical fitness in male adolescences. Sleep quality and parent education also influence physical fitness, but they had the opposite direction. All those factors should be considered as key factors in order to enhance physical fitness in male adolescences.Keywords: physical exercise, sleep quality, physical fitness, male adolescenceCorrespondence: Hayu Andita Satriani. Masters Program in Public Health, Universitas Sebelas Maret, Jl, Ir. Sutami 36 A, Surakarta, 57126, Central Java, Indonesia. Email: hayuandita@gmail.Journal of Health Promotion and Behavior (2018), 3(4): 270-278https://doi.org/10.26911/thejhpb.2018.03.04.07